Quark-hadron Phase Transition in Proto-Neutron Stars Cores based on a Non-local NJL Model - Malfatti, Germán (2017)
We study the QCD phase diagram using a non-local SU(3) NJL model with vector interactions among quarks. We analyze several thermodynamic quantities such as entropy and specific heat, and study the influence of vector interactions on the thermodynamic properties of quark matter. Upon imposing electric charge neutrality and baryon number conservation on the field equations, we compute models for the equation of state of the inner cores of proto-neutron stars providing a non-local treatment of quark matter for astrophysics.